Perspectivas en los Laboratorios de Fabricación Digital en Latinoamérica - Herrera Polo, Pablo C. (2012)
Latin American experiences are analyzed in order to identify adverse factors, describing the complexity of the implementation of a Fabrication Laboratory in the region. As a starting point we take the implementation done by groups of academics coming back to their origin countries, and others that after the implementation they were born or adapted to an academic supervision (Fab Lab MIT) or a technical and commercial one (Rhino FabLab). In the whole, the results allow to identify opportunities for the future.